Informativni razgovori - Kabil, Namik (Bosnia and Hercegovina : Sarajevo Center for Contemporary Art, 2007)
An investigation of the trauma and denial, which have become a dominant – but silent – dimension of everyday life in the post-war Bosnia and Herzegovina. Director Namik Kabil interviews a group of eyewitnesses of the war in Bosnia and Herzegovina in a rusty, dingy, deserted shed. They sit at a table, plastic cup of coffee and ashtray within reach, harshly lit by fluorescent light - as if it were an interrogation. Kabil films them with a handheld camera, against a background of grimy tiles, asking elementary questions about the war. "When did the war start for you?" "What did you eat?" "Did you see dead people?" "Did you learn anything from the war?" And especially, "do we need to talk about the war?" With one exception, they all think they do, but they say many people prefer to keep silent about it. "It's like when you have an elephant in the middle of the room," a woman says, "and everyone pretends it's not there." They talk about their experiences in Sarajevo, in the trenches or abroad, about their dulled feelings, about the solidarity during the war. But despite Kabil's repeated attempts to find out who shot at them, the interviewees still lack the courage to discuss it. "We didn't shoot at ourselves" is one woman's way of evading the question. But to the question as to who won the war, the answer is unanimous: "No one."
Verzio Film Festival Submission
Duration: 00:42:00
Verzio Film Festival Submission
Keywords: Documentary films